The Influence Of Operations Management On Patient Satisfaction With Service Quality As Mediation In Inpatient Care At Rsmj - Dyah Ning Indra; Heru Suswojo; Sholihul Absor (Global Journal of Health Administration, 2025)
Objective: This study analyzes the effect of operational management on patient satisfaction with service quality as a mediating variable in inpatient care.   Methods: A quantitative cross-sectional study was conducted on 120 adult inpatients (≥48 hours) using convenience sampling. Data were collected through SERVQUAL-based questionnaires and patient satisfaction using a five-point Likert scale. Analysis used multiple linear regression and the Sobel test (α = 0.05).   Results: Operational management had a positive effect on patient satisfaction (β = 0.189; p = 0.020), while service quality showed a significant effect (β = 0.705; p < 0.001). The R² value of 0.749 indicates a 74.9% contribution. The Sobel test (Z = 7.24; p < 0.001) confirmed the mediating role of service quality.   Conclusion: Operational management and service quality significantly influence patient satisfaction, with service quality as a key mediator.